IMPLEMENTASI, FUNGSI MASJID PARIPURNA - Zaili Rusli, Vinni Helvionita, Meyzi Heriyanto, (Jurnal Ilmu Administrasi Negara, 2019)
Implementation, Function of the Plenary Mosque. This study aims to determine andanalyze the implementation of the function of the Plenary Mosque Level District in PekanbaruCity and its supporting and inhibiting factors. This research method uses descriptive qualitativemethod. The research informants were Vice Mayor Pekanbaru, Kabag Kesra, Chairman of theBoard of Trustees, Staff, Chairperson of the Mosque and Jamaah. Data collection techniquescarried out by interview, observation, and documentation. The results showed that the PekanbaruCity Regulation Number 2 Year 2016 regarding the implementation of the Function of the PlenaryMosque at the District level in Pekanbaru City had not been implemented optimally. This is seenbased on the behavioral elements of program implementers who are not aware of their duties torealize the functions of the Plenary Mosque in the fields of idarah, imarah, and ria’ayah.